An Algorithm for the Strong-Coupling of the Fluid-Structure Interaction Using a Staggered Approach. (20th June 2012) - Pedro, Josè C.; Sibanda, P.
Abstract : We present a staggered approach for the solution of the piston fluid-structure problem in a time-dependent domain. The one-dimensional fluid flow is modelled using the nonlinear Euler equations. We investigate the time marching fluid-structure interaction and integrate the fluid and structure equations alternately using separate solvers. The Euler equations are written in moving mesh coordinates using the arbitrary Lagrangian-Eulerian (ALE) approach and discretised in space using the finite element method while the structure is integrated in time using an implicit finite difference Newmark-Wilson scheme. The influence of the time lag is studied by comparing two different structural predictors.